دور العدالة التوزيعية في تحقيق الانتماء العاطفي للمنظمة دراسة ميدانية على المشافي الجامعية بمدينة دمشق - الخزاعي, ماهر علي (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف هذا البحث لمعرفة أثر إدراك العاملين في المشافي الجامعية للعدالة التوزيعية على انتمائهم العاطفي لها ، وقد تم إتباع الأسلوب الكمي الإحصائي التحليلي في اختبار الفرضيات، وذلك بتوزيع الاستبيانات على عينة (طبقية) من الأطباء والممرضين والعاملين في المشافي الجامعية وعددهم (372) فرد , وقد توصلت الدراسة إلى أن العاملين يدركون عدم وجود عدالة توزيعية في المشافي الجامعية, كما أن مستوى انتمائهم العاطفي للمشفى ضعيف، وقد كان هنالك ارتباط معنوي إيجابي بين العدالة التوزيعية والانتماء العاطفي، بحيث إن نقص العدالة التوزيعية أثر سلباً على الانتماء العاطفي , كما أظهرت النتائج وجود فروق جوهرية بين العاملين فيما يتعلق بإدراكهم للعدالة التوزيعية تبعاً للمتغيرات الديموغرافية، (العمر، الجنس، التخصص، المستوى التعليمي، سنوات الخبرة), كما تبين وجود فروق جوهرية بين العاملين فيما يتعلق بالانتماء العاطفي تبعاً للمتغيرات الديموغرافية (العمر، التخصص، المستوى التعليمي، سنوات الخبرة), باستثناء متغير الجنس حيث لم يظهر فرق بين الذكور والإناث فيما يتعلق بمستوى إدراكهم للانتماء العاطفي. وقد توصلت الدراسة إلى مجموعة من التوصيات من أهمها: 1- أهمية مراعاة توزيع الأعباء الوظيفية على العاملين بشكل عادل ومناسب ، وهذا الأمر يؤدي إلى زيادة مستوى إحساس الموظفين بعدالة التوزيع بحيث تتناسب أعبائهم الوظيفية مع مؤهلاتهم وقدراتهم،وتناسب الراتب مع الجهد المبذول. 2- العمل على زيادة مستوى الانتماء العاطفي لدى العاملين من خلال توفير العدالة التوزيعية لما لذلك من دور مهم في زيادة التصاق العاملين بمنظماتهم (المشافي) ورفع روحهم المعنوية ،بما يتيح اندفاعهم للعمل بتعاون وحماس كبير لتحقيق الأهداف التنظيمية المرغوبة. This research aims to determine the impact of perception employed in university hospitals of distributive justice on their emotional affiliation to those hospitals, quantitative analytical method has been followed to test hypothesis by distributing questionnaires to a sample of (372) person of Doctors, nurses and staff at those university hospitals. The statistical analyses refer to the following results: Workers do not realize that there is a distributive justice at university hospitals; also , the level of emotional affiliation to those hospitals was weak. There is a significant positive correlation between distributive justice and emotional affiliation . There are significant differences between workers with respect to distributive justice according to demographic variables (age ,sex, specialty, level of education, and years of experience). Also there are differences significant among workers with regard to emotional belonging depending on the demographic variables (age, specialty, level of education, years of experience) except sex. The study found a set of recommendations including: 1 - The importance of taking into account the distribution of functional burden on workers fairly and appropriately, and this leads to increase the level of staff distributive justice sense that any functional burdens fit with their qualifications and abilities, and that salary fits with exertion. 2 - The need to develop the understanding of workers to emotional affiliation, because of its important role in raising the morale of workers and making them love their work and their organization, which pushes them to work collaboratively and with great enthusiasm to achieve the desired organizational goals.